(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Sustainable entrepreneurship serves at the nexus of economic viability, ecological stewardship, and social responsibility. However, the prevailing Triple Bottom Line (TBL) framework, which treats these aspects as harmoniously aligned, fails to adequately capture the ongoing conflicts entrepreneurs face when balancing sustainability objectives. This limitation has created a theoretical gap in understanding how sustainability-related contradictions can generate entrepreneurial innovation. Therefore, this study aims to examine the limitations of the TBL framework, synthesise insights from paradox theory and the sustainable entrepreneurship literature, and propose a novel conceptual model that explains how sustainability tensions can become sources of innovation. The study is based on conceptual theory-building research design grounded in a systematic review and synthesis of the literature on sustainable entrepreneurship, paradox theory, and the Triple Bottom Line. Through thematic analysis and theory synthesis, key concepts, tensions, and mechanisms underlying sustainable entrepreneurial action were identified and integrated. The study proposes the Paradox Field Model of Sustainable Entrepreneurship. Economic sustainability, social sustainability, ecological sustainability, and entrepreneurial innovation comprise the four interrelated dimensions of the three-dimensional tetrahedral framework. The model identifies six persistent paradoxical tensions and explains how entrepreneurs transform these tensions into innovative outcomes through five mechanisms: tension recognition, rethinking cognitive, both/and thinking, dynamic cycling, and tetrahedral integration. The study concludes that sustainability tensions should not be viewed as obstacles to be resolved but as productive forces that stimulate entrepreneurial innovation, offering a new theoretical foundation for future research and practice in sustainable entrepreneurship.